2022
DOI: 10.3390/nu14153158
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Supplementation with Cardiovascular Events: A Systematic Review and Meta-Analysis

Abstract: Background: low vitamin D status has been associated with an increased incidence of cardiovascular events. However, whether vitamin D supplementation would reduce the incidence of cardiovascular events remains unclear. Purpose: To perform a systematic review and meta-analysis of the effect of vitamin D supplementation on the mortality and incidence of cardiovascular events. Data Sources: We searched Medline, Embase, and the Cochrane Central Register of Controlled Trials from their inception until 3 May 2022. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In the meta-analysis from Barbarawi et al (2019) including 21 RCTs for a total of 83,291 participants (of whom 41,669 received vitamin D and 41,622 received placebos), no association was observed between vitamin D supplementation and reduced risk of major adverse cardiovascular events as defined by each trial (primary endpoint), or AMI, stroke, CVD mortality, and all-cause mortality (secondary endpoints) [ 180 ]. A more recent systematic review and meta-analysis (18 RCTs published by May 2022, with a total of 70,278 participants eligible for analysis) confirmed the lack of association of vitamin D supplementation with mortality of cardiovascular events as well as with incidence of AMI, stroke, total cardiovascular events or cerebrovascular events [ 181 ]. Previously, a Cochrane Library Review concluded that vitamin D supplementation decreased all-cause mortality (75,927 participants; 38 trials), but only when supplemented with vitamin D3 (RR = 0.94 95% CI: 0.91–0.98), whereas vitamin D2, alfacalcidol, or calcitriol had no effects on mortality [ 182 ].…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meta-analysis from Barbarawi et al (2019) including 21 RCTs for a total of 83,291 participants (of whom 41,669 received vitamin D and 41,622 received placebos), no association was observed between vitamin D supplementation and reduced risk of major adverse cardiovascular events as defined by each trial (primary endpoint), or AMI, stroke, CVD mortality, and all-cause mortality (secondary endpoints) [ 180 ]. A more recent systematic review and meta-analysis (18 RCTs published by May 2022, with a total of 70,278 participants eligible for analysis) confirmed the lack of association of vitamin D supplementation with mortality of cardiovascular events as well as with incidence of AMI, stroke, total cardiovascular events or cerebrovascular events [ 181 ]. Previously, a Cochrane Library Review concluded that vitamin D supplementation decreased all-cause mortality (75,927 participants; 38 trials), but only when supplemented with vitamin D3 (RR = 0.94 95% CI: 0.91–0.98), whereas vitamin D2, alfacalcidol, or calcitriol had no effects on mortality [ 182 ].…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…In summary, results from interventional studies, in general, do not support the routine use of vitamin D supplementation, although this strategy could be useful in certain subgroups, where its use may improve metabolic parameters, reducing oxidative stress, inflammation, and CV outcomes [ 199 ]. However, it should be noted that the small sample size, the relatively short duration of vitamin D supplementation, and heterogeneity in terms of vitamin D dose, duration of treatment, comorbid conditions, population characteristics, choice of oxidative or inflammatory biomarkers, and assessment of baseline 25(OH)D level across trials could affect the reported results [ 181 ].…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…A more recent systematic review (Pei et al, 2022) on vitamin D supplementation (with or without calcium co-supplementation) and CVD incidence and mortality included 18 RCTs (70,278 participants) lasting between 1 and 6 years which provided yearly, monthly, weekly, or daily doses of vitamin D corresponding to daily doses between 10 and 100 μg/day, and up to 2,500 μg/day in one study (Brohult et al, 1973). No differences between vitamin D and placebo groups were reported for CVD mortality (9 trials; 63,227 participants; 736 vs. 759 events), myocardial infarction (14 trials; 46,194 participants; 552 vs. 566 events) or stroke (12 trials; 46,093 participants; 437 vs. 413 events), or in sensitivity analyses considering the number of subjects, number of events, vitamin D dose, pattern of administration, serum 25(OH)D at baseline and duration of the intervention.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…223 Meta-analyses, although limited by the fact that some included studies where CVD outcomes were not the primary endpoints, have shown no significant reduction in mortality and cardiovascular risk with vitamin D supplementation. [224][225][226] Recently, Pei et al 227 found no effect of vitamin D supplementation on mortality and incidence of cardiovascular events in a meta-analysis of 18 trials (70,278 participants). Another meta-analysis of RCTs evaluating mortality effect of vitamin D supplementation compared with placebo or no treatment found that, while vitamin D supplementation significantly reduced risk of cancer death, it had no effect on all-cause mortality or cardiovascular mortality.…”
Section: Vitamin Dmentioning
confidence: 99%